Russian perspectives - Torelli, Giuseppe 1658-1709; Čajkovskij, Pëtr Ilʹič 1840-1893; Rachmaninov, Sergej Vasilʹevič 1873-1943; Rubinštejn, Anton G. 1829-1894; Gedike, Fëdor Karlovič 1839-1916; Honegger, Arthur 1892-1955; Hindemith, Paul 1895-1963; Enescu, George 1881-1955; Martini, Giovanni Battista 1706-1784; Giazotto, Remo 1910-1998; Mozart, Wolfgang Amadeus 1756-1791 (International Trumpet Guild, 2015)
The disc in your hands is a compendium of recordings done between 1959 and 2011 by the outstanding Russian trumpeter Vadim Novikov (b. 1941), whose longtime professional activities have been focused on establishing the trumpet as a solo instrument and as a consistent participant in the concert life of Russia. - Container
Issued with ITG Journal, vol. 39 no. 4 (June 2015). - "Not for sale. This CD is free to all 2014-2015 ITG members" - Container. - Program notes in English by Inessa Svirida and James Olcott printed on container
The 1st work for trumpet and string orchestra; the 2nd, 7th and 8th works originally for piano, arranged for trumpet and piano; the 3rd, 5th and 6th works originally for voice and piano, arranged for trumpet and piano; the 4th work is a ballet excerpt, arranged for trumpet and piano; the 13th work originally for organ, arranged for trumpet and organ; the 14th work originally for organ and string orchestra, arranged for trumpet and organ; the 15th work is an opera excerpt, arranged for trumpet and orchestra
Interpreten: Vadim Novikov, trumpet ; Svetlana Orudzheva (tracks 4, 7-12, 16), Yulia Kogan (tracks 5-6), Mikhail Mishin (tracks 13-15), piano ; Boris Romanov (track 17), Alexey Shmitov (track 18), organ ; Moscow Chamber Orchestra, Anatoly Knorre, conductor (tracks 1-3) ; orchestra students of the P.I. Tchaikovsky Moscow State Conservatory, Leonid Nikolaev, conductor (track 19)
Aufnahmen: 1958, 1996, 2011, 1971, 1996, 2007
Keywords: Concertos (Trumpet with string orchestra); Trumpet and piano music, Arranged; Waltzes; Ballets / Excerpts, Arranged; Sonatas (Trumpet and piano); Trumpet and piano music; Trumpet and organ music, Arranged; Canons, fugues, etc. (Trumpet and organ); Operas / Excerpts, Arranged; Trumpet with orchestra, Arranged